A retrospective, longitudinal study of rheumatoid arthritis treatment patterns with Janus kinase inhibitors and other disease-modifying antirheumatic drugs in Japan. Issue 3 (27th May 2022) - Kaneko, Yuko; Sakurai, Masaya; Snijder, Robert; Kokubo, Satoshi; Kato, Daisuke
ABSTRACT: Objectives: There is limited information on the clinical use of Janus kinase inhibitors (JAKis) for rheumatoid arthritis treatment in Japan. The aim of this study was to identify disease-modifying antirheumatic drug (DMARD) treatment patterns in Japan. Methods: This retrospective, longitudinal study extracted data from the Japan Medical Data Center database. Patients with rheumatoid arthritis diagnosis were enrolled 2016–19, during which patients had a first prescription of a major DMARD, split into six mutually exclusive classes: methotrexate (MTX); other conventional synthetic DMARDs; tumour necrosis factor alpha inhibitors; cytotoxic T-lymphocyte-associated antigen-4-immunoglobulin; anti-interleukin-6 receptor therapies; and JAKis. The primary objective was to describe DMARD treatment patterns, especially for JAKis. Results: Overall, 10, 399 patients were included in the analysis. The most common treatments were MTX, other conventional synthetic DMARDs, and tumour necrosis factor alpha inhibitors. The total number of JAKi prescriptions increased approximately 8-fold during 2016–19. Most (61.1%) patients who received JAKis had prior MTX or tumour necrosis factor alpha inhibitor treatment. The duration of JAKi treatment was longer than for biologics and other conventional synthetic DMARDs and comparable to that of MTX. Conclusions: The sequence of drug class prescriptions for rheumatoid arthritis in Japan during 2016–19 followed clinical guidelines. Over this period, JAKis were increasingly used as a second-line treatment following MTX.